1992
DOI: 10.1093/ajh/5.7.431
|View full text |Cite
|
Sign up to set email alerts
|

Renal Resistive Index After Captopril Test by Echo-Doppler in Essential Hypertension

Abstract: In 45 patients with essential hypertension and 15 age-matched normotensive control subjects, the renal resistive index, as an expression of arterial impedance, was determined using Doppler ultrasound. In both kidneys the resistive index was assessed at baseline and after captopril test (50 mg orally). In the moderate and severe hypertensives, compared to mild hypertensives and control subjects, the baseline resistive index was significantly higher (P less than .05). Following captopril, the resistive index inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 0 publications
1
28
1
1
Order By: Relevance
“…In a Veglio et al [25] study including a relatively small group of 45 patients with essential HT it was shown that RRI was higher in subjects with a long-standing HT as compared to normotensive subjects and correlated with the severity and duration of the disease. The authors reported that baseline RRI was significantly higher in moderate and severe HT when compared to normal subjects and patients with mild HT [2,10,21,25].…”
Section: Discussionmentioning
confidence: 96%
“…In a Veglio et al [25] study including a relatively small group of 45 patients with essential HT it was shown that RRI was higher in subjects with a long-standing HT as compared to normotensive subjects and correlated with the severity and duration of the disease. The authors reported that baseline RRI was significantly higher in moderate and severe HT when compared to normal subjects and patients with mild HT [2,10,21,25].…”
Section: Discussionmentioning
confidence: 96%
“…Poor control of blood glucose, as represented by increased HbA 1c , and basal PRA affected the magnitude of decrease in RI in patients with type 2 diabetes. Veglio et al (15) reported that in healthy subjects and patients with mild hypertension, RI values of interlobar arteries after the captopril (50 mg) test were significantly higher than those before the captopril test. In the present study, RI values in the control subjects were significantly increased after the captopril test, being consistent with the results of Veglio et al, despite the difference between studies in the dose of captopril used.…”
Section: Factors Associated With ⌬Ri In Diabetic Patientsmentioning
confidence: 99%
“…Thus currently, RRI is accepted as a well-known marker of renal vascular and interstitial damage, corresponding to an increased total cardiovascular risk (10). To this regard we can cite a study where RRI, measured at interlobar arteries, shown to be associated with the severity and duration of essential hypertension (11) while in 426 patients with essential hypertension was also demonstrated that impairment of renal hemodynamics, as assessed by an increased RRI, was associated with an increased risk of cardiovascular and renal outcomes (12). Moreover it is also known that RRI decreases with use of renin angiotensin system (RAS) inhibitors, due to the hemodynamic changes induced by these antihypertensive agents.…”
Section: Introductionmentioning
confidence: 99%